The Digital Kampung: The Role of Mediated Communication in Indonesia's Online Community Dynamics (Universitas Terbuka, 2025)
Emergence of new communities in digital age The advent of digitized era in Indo- nesia and the further development of personal computing are substituting some links between people that they used to be face-to-face be- fore. Thus, developing community implies more than ever before a virtual space which could never create without technology (Habermas, 1994; Wellington et al., 2016). This paper analyses these “digital kampung” spaces through the lens of Mediatization Theory and Cultural Proximity Theory. The analysis takes places through the lens of qualitative content analysis, focusing on patterns in communicative practices across selected community-based Facebook groups, WhatsApp networks and local marketplace platforms. Against this backdrop, the paper explains how mediated communication transforms gotong royong (mutual aid) into hybrids that integrate online coordination with offline enactment. Cultural affinity remains an influence, since common language, symbols and stories that have to do with the place help members feel as if they belong even when they are scattered all over. But the findings also capture tensions: for example between misinformation and lack of access to digital tools, and shifts in what is considered trust. Ultimately the digital kampung is both the continuation and also an adaptation of age old communal traditions in Indonesia, it illustrates how technological platforms can facilitate social coher- ence whilst responding to some of the complex cultural contexts between urban–rural divides.